SAT0685 USE AND IMPACT ON SOCIAL NETWORKS BY RHEUMATOLOGY JOURNALS. (June 2019) - Fernández-Ávila, Daniel G.; Ávila, Vaneza; Muñoz, Oscar; García, Angel
Abstract : Background: Traditional system for assessing the quality and impact of a scientific journal is based on the number of citations. One of the main forms of measurement is the impact factor, which measures the impact that a journal has on the scientific community. Despite its traditional use, this quality and impact assessment system has been criticized in recent years. The "Alternative Assessment Metrics" initiative (Altmetrics) seeks to define new measures of metrics for scientific publications 1 . Alternative metrics are based on the number of "mentions" of an article in various online sources, including blogs and social networking platforms 2 . The alternative metrics are more dynamic and accumulate quickly in real time. The social networks most frequently used by scientific journals are Facebook, YouTube and Twitter Objectives: To evaluate presence, number of followers and activity of rheumatology journals in 3 social networks (Facebook, Twittter and Youtube). Methods: Platform of scientific journals SCOPUS was consulted, selecting journals classified as rheumatology journals. Scimago Journal Rank (SRJ) of 2017 was taken to evaluate the quality of the journal. The social networks Facebook, Twitter and YouTube were consulted, searching for rheumatology journals of those found in SCOPUS with active accounts in these social networks. Date of consultation: 13-11-18 Results: 61 rheumatology journals in SCOPUS, of which only 8 (13.1%) had an active account in at least one of the social networks consulted. On Facebook the most active and most popular magazine was Nature Reviews, followed by the Journal of Rheumatology and Annals of the Rheumatic Diseases. It should be noted that Nature Reviews includes other journals in their social networks that cover other specialties of medicine such as cardiology, immunology, microbiology, oncology, among others. On Twitter, as on Facebook, magazine with largest number of followers was Nature Reviews, followed by Annals of the Rheumatic Diseases and Journal of Rheumatology. Activity on Twitter, measured as number of twits, had same behavior according to the number of followers. The only journal with channel on YouTube was Annals of the Rheumatic disease with 67 subscribers, 12 videos, of which the most watched has 315 reproductions. See table 1 Conclusion: YT and FB are social networks with a high content of false information. The majority of available videos promise to cure different rheumatic diseases (even several simultaneously). This is the first work of a line of research that seeks to highlight the high degree of misinformation. We will continue to analyze other diseases and social networks, to make publications and communications in different media and to alert local regulatory entities. References: [1] Trueger NS, Thoma B, Hsu CH, et al. The Altmetric Score: a new measure for article-level dissemination and impact. Ann Emerg Med 2015; 66:549–53. [2] Maggio LA, et al. Beyond Citation Rates: A Real-Time Impact Analysis of Health Professions Education Research Using Altmetrics. Acad Med 2017;92:1449-55 Disclosure of Interests: None declared